2008
DOI: 10.1098/rsbl.2008.0279
|View full text |Cite
|
Sign up to set email alerts
|

The modelling of avian visual perception predicts behavioural rejection responses to foreign egg colours

Abstract: How do birds tell the colours of their own and foreign eggs apart? We demonstrate that perceptual modelling of avian visual discrimination can predict behavioural rejection responses to foreign eggs in the nest of wild birds. We use a photoreceptor noise-limited colour opponent model of visual perception to evaluate its accuracy as a predictor of behavioural rates of experimental egg discrimination in the song thrush Turdus philomelos. The visual modelling of experimental and natural eggshell colours suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 27 publications
7
122
0
Order By: Relevance
“…That the rejection of foreign eggs does not depend on the degree of contrast between eggs and the nest lining (this study) provides support for earlier findings in hosts of egg-mimetic brood parasites that egg rejection is driven mechanistically by differences between foreign and own eggs (Cassey et al, 2008;Stevens et al, 2013;Moskat et al, 2014b). In contrast, cowbird eggs in robin nests are exceptional to this pattern: Croston and Hauber (2014a) showed that while robins' responses to artificial egg colors are generally predicted by chromatic JNDs differentiating foreign versus host eggs, artificial cowbird ground color-mimetic (beige) eggs are rejected in 100% of trials, despite their relatively low avianperceivable chromatic difference from robin eggs (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…That the rejection of foreign eggs does not depend on the degree of contrast between eggs and the nest lining (this study) provides support for earlier findings in hosts of egg-mimetic brood parasites that egg rejection is driven mechanistically by differences between foreign and own eggs (Cassey et al, 2008;Stevens et al, 2013;Moskat et al, 2014b). In contrast, cowbird eggs in robin nests are exceptional to this pattern: Croston and Hauber (2014a) showed that while robins' responses to artificial egg colors are generally predicted by chromatic JNDs differentiating foreign versus host eggs, artificial cowbird ground color-mimetic (beige) eggs are rejected in 100% of trials, despite their relatively low avianperceivable chromatic difference from robin eggs (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Chromatic distance is but one component of broader sensory/perceptual (de la Colina et al, 2012) and cognition-dependent (Hauber and Sherman, 2001;Moskát and Hauber, 2007;Croston and Hauber, 2015) processes that ultimately result in the complex behavioral decision to accept or reject a parasitic egg. For example, there are a growing number of studies showing that perceptual difference alone does not fully explain patterns of egg rejection behavior (Moskát and Hauber, 2007;Moskát et al, 2010;Cassey et al, 2008;Stoddard and Stevens, 2011;Bán et al, 2013;Stevens et al, 2013;Croston and Hauber, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…In the light of recent advances in analyzing color differences as seen by nonhuman animals (6, 7), three studies have used advanced perceptual models of avian discrimination to investigate cuckoo and host egg coloration (8)(9)(10). These confirmed that quantification of visual signals used by hosts to detect parasitism provides much greater insights when analyzed with models of bird vision than does subjective human assessment (5).…”
mentioning
confidence: 93%
“…Rothstein, 1982;Underwood and Sealy, 2006). Cognitive mechanisms which correspond to contextdependent egg discrimination (Rothstein, 1975;Welbergen et al, 2001;Lahti and Lahti, 2002;Hauber et al, 2006;Moskát and Hauber, 2007), including the avian-specific sensory perception of egg coloration (Avilés, 2008;Cassey et al, 2008a;Cassey et al, 2008b;Safran and Vitousek, 2008;Langmore et al, 2009), seem to be key factors in explaining behavioural variability of rejection decisions in host-brood parasite co-evolution. Nonetheless, the extent to which variability in the host's flexibility of speciesrecognition systems impacts on adaptive responses to parasitism (Sherman et al, 1997;McLean and Maloney, 1998;Stokke et al, 2005;Hauber et al, 2006;Moskát and Hauber, 2007) remains to be fully understood.…”
Section: Introductionmentioning
confidence: 99%